Epidemiological study on dog bite presenting at district hospital in Karnali province of Nepal - Moharab, Shekh; Gautam, Aaditya; Moktan, Prashant; Khadka, Bijaya Singh; Sharma, Pratikshya; Khatun, Noorjahan; Poudel, Siddhartha; Dhakal, Rojina; Parajuli, Apekshya; Saud, Dhruba; K.C., Shreejana; Swarnkar, Kabita Sah; et al. (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Worldwide, dog bite is a serious health concern which can lead to severe injury and endemic diseases like rabies. Particularly because of dog bites, Nepal is a rabies-endemic country. Dailekh District has been noted for the high incidence of dog bites. However, studies in this area remain scarce. Hence, this study aimed to find the epidemiological patterns of dog bite cases registered in the Dailekh District Hospital, Nepal.Method: A descriptive cross-sectional study was conducted using secondary data from the Dailekh District Hospital. A total of 659 dog bite cases were registered during October 2023 to September 2024. Data were entered and analyzed in SPSS 26.0. Descriptive analysis was done.Result: Out of 659 dog bite cases, no death was reported. The highest number of cases 234(35.5%) was recorded in winter, primarily in January 102 (15.5%) cases indicating the peak season for dog bites. Most cases 653(99.1%) originated from Dailekh District, primarily from Narayan Municipality 340 (52.1%) cases, with the highest incidence observed in Wards 08, 09, and 11. Out of total cases, 385(58.4%) were males and 325(49.3%) were below 20 years of age. However, the highest incidence was seen in the 80+ Years age group.Conclusion: Dog bite is highly prevalent in Dailekh District, particularly during winter season. It is more common among males, children, adolescents and elder population. Targeted interventions such as public awareness programs and rabies prevention strategies are recommended particularly in areas with high incidence and high-risk groups of Dailekh District.